Environmental triggers for connective tissue disease: the case of COVID-19 associated with dermatomyositis-specific autoantibodies. Issue 6 (November 2021) - De Santis, Maria; Isailovic, Natasa; Motta, Francesca; Ricordi, Caterina; Ceribelli, Angela; Lanza, Ezio; Azzolini, Elena; Badalamenti, Salvatore; Voza, Antonio; Selmi, Carlo
Abstract : Purpose of review: The aim of the present review is to analyze the link between autoimmune diseases and environmental factors, in particular severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (COVID-19) as it shares numerous features with the interstitial lung disease associated with connective tissue diseases positive for rare autoantibodies directed at highly specific autoantigens (i.e., MDA5 and RIG1) among the intracellular sensors of SARS-CoV-2 in the innate response against viruses. Recent findings: As shown in recent publications and in our original data, specific autoantibodies may be functionally relevant to COVID-19 infection. We evaluated sera from 35 hospitalized patients with COVID-19 to identify antinuclear antibodies and autoantibodies directed against specific antigenic targets, and we identified anti-nuclear antibodies (ANA) in 20/35 of patients with COVID-19 (57%), in patients with need for supplemental oxygen (90% vs. 20% in ANA-negative cases; P  < 0.0001). In 7/35 COVID-19 sera, we detected anti-MJ/NXP2 ( n  = 3), anti-RIG1 ( n  = 2), anti-Scl-70/TOPO1 ( n  = 1), and anti-MDA5 ( n  = 1), overall associated with a significantly worse pulmonary involvement at lung computerized tomography scans. Eleven (31%) patients were positive for antibodies against the E2/E3 subunits of mitochondrial pyruvate dehydrogenase complex. Summary: Viral infections such as COVID-19 are associated with ANA and autoantibodies directed toward antiviral signaling antigens in particular in patients with worse pulmonary involvement.